Analisis Faktor-faktor Penerimaan Pengguna Website E-Learning pada UHW PERBANAS Surabaya Menggunakan Metode UTAUT - Alief, Muhammad Dian Nur; Pratama, Arista; Wulansari, Anita (Journal of Computer Science and Information System(JCoInS), 2024)
Information and communication technology (ICT) continues to spread throughout all spheres of life, including education. UHW PERBANAS SURABAYA, uses data and correspondence innovation in instructing and advancing by utilizing the UHW PERBANAS SURABAYA E-Learning Site. However, in its application there are several problems when submitting opinions / answers to the discussion session. The column box that has been provided likes to disappear by itself or error by itself and in e-learning there is a limited size or size so that it cannot collect or send assignments with large file sizes, so it is required to compress the file first. This study intends to break down the variables that impact client (understudy) acknowledgment of the UHW PERBANAS SURABAYA E-Learning Site. This examination utilizes the UTAUT (Bound together hypothesis of Acknowledgment and Utilization of Innovation) research model. Testing utilizing Proportionate Delineated Arbitrary Inspecting procedure. A sample size of 347 respondents from UHW PERBANAS Surabaya students was used for the online data collection. The exploration information were investigated utilizing SEM-PLS with WarpPLS 6.0 programming. In light of the consequences of the examination, it is found that presentation hope, exertion hope, social impact meaningfully affect understudies' aim to utilize E-learning. Furthermore, working with conditions and social aim likewise decidedly affect understudy utilization conduct on E-learning.